PENGARUH METODE PEMBELAJARAN KWL (KNOW, WANT, LEARN) DAN MINAT MEMBACA TERHADAP HASIL BELAJAR READING COMPREHENSION - Harismawan Muhtarif, Ahmad; Suherman; Luluk Asmawati (Cakrawala Pedagogik, 2023)
This research aims to investigate the impact of the Know, Want To Know, Learned (KWL) learning method and students' interest in reading on the learning outcomes of reading comprehension in VIII class of MTs Daar el-Qolam IV. The study is motivated by the low English language learning outcomes in the understanding concept and the lack of reading interest among students. Therefore, the researcher implements the KWL model to address the challenges faced by the students. The method employed in this research is an experiment with a 2x2 treatment by level design. The population consists of all VIII students of MTs Daar el-Qolam IV, totaling 191 students. The sample was taken using the simple random sampling technique, comprising 76 students divided into two groups; the experimental class (A1) being class VIII-B with 36 students, and the control class (A2) being class VIII-C with 40 students. The research findings indicate that (1) the KWL model is more effective when used by students compared to the conventional method commonly used, namely the Think Pair Share (TPS) method. (2) Additionally, the results also demonstrate that students with a high interest in reading have higher learning outcomes compared to students with low reading interest. (3) There is an interaction between students who undergo the learning process using the KWL method and students using the TPS learning method. (4) Students with high reading interest in the KWL group have higher reading comprehension learning outcomes compared to students in the TPS group, even though they both have high reading interest. And (5) Students in the KWL group with low reading interest also have high reading comprehension learning outcomes compared to students in the TPS group with low reading interest.